Ethnic Homogamy and Interethnic Marriages in Tuva: Evidence from the 2021 All-Russian Population Census - Rostovskaya, Tamara K.; Fauzer, Viktor V.; Sitkovskiy, Arsenii M. (The New Research of Tuva, 2026)
The article examines the scale, structure, and gender-ethnic configuration of interethnic married couples in Tuva based on data from the 2021 All-Russian Population Census (published results on the ethnic composition of the population, as well as Rosstat data on the distribution of married couples by spouses’ ethnicity). The study employs methods of descriptive demographic statistics, matrix analysis of married couples, calculation of the shares of ethnically homogamous and interethnic unions, and assessment of gender asymmetry in Russian–Tuvan marital combinations.It is shown that among 49,964 married couples in Tuva in which both spouses reported their ethnicity, 48,702 couples are ethnically homogeneous, while 1,262 (2.53%) are interethnic. A central feature of Tuva’s marital structure is the extremely high homogamy among Tuvans and the concentration of mixed unions around the Russian–Tuvan pairing, which accounts for 555 couples (44.0% of all interethnic married couples).The results refine current understandings of interethnic marriage in Tuva and demonstrate that the statistical rarity of mixed marriages should be interpreted not only through the numerical ratio of ethnic groups, but also through the persistence of social boundaries, as revealed by marital status statistics.
Keywords: Tuvans; Russians of Tuva; interethnic marriage; ethnic homogamy; married couple; ethnicity; All-Russian Population Census; ethno-demography; Tuva; Republic of Tuva